Surface treatment of aluminium automotive sheet: Mythology and technology. (3rd May 2013) - Scamans, G. M.; Andrews, P. R.; Butler, C.; Hall, A.; Thompson, G. E.; Ma, Y.; Zhou, X.
Abstract : The use of aluminium automotive sheet to save weight, fuel and carbon emissions is increasing as EU OEMS strive to reach progressively tougher targets and from the need to avoid fleet average penalty payments. Surface finishing of structural sheet for alloys like AA5754 generally involves cleaning and pretreatment followed by roll coating with a lubricant. For alloys supplied for body panels like AA6016 and its variants, surface treatments can include a mechanical texturing treatment followed by cleaning and pretreatment with a stabilising treatment and then spray coating with a dry film lubricant. Surface finishing capacity in the EU is now available on six finishing lines with an estimated total capacity of about 350 kt/year. This is just about in balance with present demand, but the capacity of the existing lines will soon be exceeded by the rapidly increasing demand. Further finishing lines will be required to keep pace with the increasing demand. There is a difficult balance to achieve between cost and finishing process complexity and the demanding requirements of formability, adhesive bond durability and surface appearance specified by the automotive companies in the EU. It is important to understand the need and value of each of the finishing treatments considered to be essential for automotive sheet supply in the EU compared to the less stringent requirements applied in North America and Japan. The complex microstructural and technological issues surrounding surface finishing and sheet performance will be analysed and discussed in detail and opportunities identified. Copyright © 2013 John Wiley & Sons, Ltd.